Edukasi Kesehatan Cegah Resiko Dini Aksi Sebaya (CERDAS) - Wahyuningsih, Wahyuningsih; Fhirawati, Fhirawati; Siokal, Brajakson (Patria Artha Journal of Community (PKM), 2025)
Early marriage remains a complex social problem with broad impacts on reproductive health, education, and social welfare. In Gowa Regency, early marriage is prevalent among adolescent girls and has resulted in increased risks of pregnancy and childbirth complications, limited access to healthcare services, and reduced economic opportunities. Psychologically, adolescents who marry early are also more vulnerable to stress, depression, and restricted personal development. This community service activity was carried out in Borongloe Subdistrict for one day and involved 100 adolescents aged 15–18 years. The activities consisted of educational sessions, peer group discussions, and role-play. The educational sessions covered topics on the risks and impacts of early marriage, strategies to cope with cultural pressures within families, and the importance of maintaining adolescent reproductive health. The discussion sessions provided a space for participants to share their personal experiences related to early marriage, followed by role-play activities simulating cases of early marriage that occurred in their surroundings. The results showed a significant increase in adolescents’ knowledge and awareness regarding the risks and impacts of early marriage and the importance of maintaining reproductive health. Based on the pre-test results, 60% of participants had a low level of knowledge, while the post-test results indicated improvement, with 100% of participants demonstrating better understanding. This community service program proved to be effective in increasing adolescents’ understanding and awareness of the dangers of early marriage. It also served as a preventive effort to empower adolescents to make better decisions regarding their future and reproductive health.